Native Americans in Chris Eyre’s Smoke Signals - Földesi, Milán (AMERICANA E-journal of American Studies in Hungary, 2018)
Chris Eyre’s Smoke Signals (1998) could and should have been a milestone for Native American filmmaking. It differentiates itself from other Indian focused movies such as Dances with Wolves (1990) or The Last of the Mohicans (1992) by presenting life in a reservation with all its wonders and problems. Eyre, by adapting several stories from Sherman Alexie’s “The Lone Ranger and Tonto Fistfight in Heaven” (1993), shows aspects and issues of the contemporary Native Americans, such as the importance of their hair and their constant fight against alcoholism through the main characters, Victor Joseph and Thomas Builds-the-Fire. The aim of this article is to stress Smoke Signal’s legacy and to find out why it failed to change the way non-Natives look at the American Indians.